The role of fiscal policy on poverty reduction in South Africa - Mlungisi Mokoena; Adrino Mazenda (Future Business Journal)
Abstract This paper presents the results of ridge regression analysis of the relationship between government spending in emancipation programmes and multidimensional poverty, focusing on South Africa. Through the Principal Component analysis, we retained three variables of this relationship, affected by a range of factors, to determine the size and direction of the relationship. Besides health, we find no clear evidence that government spending on housing and social security significantly reduces multidimensional poverty. Co-production in housing, healthcare delivery, and social security should be encouraged.